Multiple Lipomatous Hemangiopericytomas in the Foot and Ankle - Pandey, Vivek (Indian J Surg, 2017)
Since its first description, the diagnosis and terminology of hemangiopericytoma have been in controversy. We report perhaps the first case of multiple lipomatous hemangiopericytoma occurring in the foot and ankle region.